Vesicovaginal Fistula After Fourteen Years of Pelvic Radiation - Tiwari, Kenusha Devi; Karki, Aruna; Dangal, Ganesh; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma (Nepal Journal of Obstetrics and Gynaecology, 2018)
Radiation therapy is an effective treatment for cervical cancer. However, of various complications, irradiation sometimes can cause formation of fistula between vagina and bladder and or rectum compromising the quality of life. Pelvic radiation is the primary cause of delayed vesicovaginal fistula with incidence of 13% in well-resourced countries and 0.2% in low resourced countries. Majority of them become apparent 1.5-2 years after completion of radiotherapy and can occur even up-to 20-30 years after the original insult. A 63 years’ female visited our outpatient department for involuntary loss of urine per vagina for 1.5 years. She had undergone radical hysterectomy and radiotherapy 16 years ago for an advanced cervical carcinoma. With positive dye test, she had vesicovaginal fistula with Goh classification of 1biii. She underwent simple fistula repair via vaginal approach. After three weeks of catheterization, successful closure was achieved.